Conflict of Beatrice Prior in Rothâ€™s Allegiant - Gusti Ayu Made Rai Suarniti (RETORIKA: Jurnal Ilmu Bahasa, 2018)
The title of this writing is â€œConflict of Beatrice Prior in Rothâ€™s Allegiantâ€. The specific aim of this scientific writing is to find out and describe the conflicts that are faced by the main character and to find out the source of the conflicts Rothâ€™s Allegiant. This novel is the third series of Divergent written by Veronica Roth and published in 2016. The data is collected through library research and analyzed based on two main theories. The main theory which is used in analyzing this paper is theory of literature by Lajos Egri and also theory of psychology by Tayla Bauer & Berrin Erdogan in his book entitled An Introduction to Organizational Behavior, This research is analyzed based qualitative-descriptive method. Based on the result of analysis, it can be concluded that Conflict of Beatrice Prior in Rothâ€™s Allegiant consist of internal and external conflict. Types of internal conflicts of Tris is categorized as Intrapersonal conflict. Meanwhile, the types of external conflicts are categorized as Interpersonal conflict and Intergroup conflict. The source of the conflict are differing in attitudes, values, and perceptions, differing in goals or objective, differing in personal style or personality.